Poultry production in hot climates - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Poultry production in hot climates edited by N J Daghir 1995 320pp ISBN 0 85198 907 1 (Hbk) price UKL49.95